The Metabolic Response of Various Cell Lines to Microtubule-Driven Uptake of Lipid- and Polymer-Coated Layer-by-Layer Microcarriers - Claudia Claus; Robert Fritz; Erik Schilling; Uta Reibetanz (MDPI AG, 2021)
Lipid structures, such as liposomes or micelles, are of high interest as an approach to support the transport and delivery of active agents as a drug delivery system. However, there are many open questions regarding their uptake and impact on cellular metabolism. In this study, lipid structures were assembled as a supported lipid bilayer on top of biopolymer-coated microcarriers based on the Layer-by-Layer assembly strategy. The functionalized microcarriers were then applied to various human and animal cell lines in addition to primary human macrophages (MΦ). Here, their influence on cellular metabolism and their intracellular localization were detected by extracellular flux analysis and immunofluorescence analysis, respectively. The impact of microcarriers on metabolic parameters was in most cell types rather low. However, lipid bilayer-supported microcarriers induced a decrease in oxygen consumption rate (OCR, indicative for mitochondrial respiration) and extracellular acidification rate (ECAR, indicative for glycolysis) in Vero cells. Additionally, in Vero cells lipid bilayer microcarriers showed a more pronounced association with microtubule filaments than polymer-coated microcarrier. Furthermore, they localized to a perinuclear region and induced nuclei with some deformations at a higher rate than unfunctionalized carriers. This association was reduced through the application of the microtubule polymerization inhibitor nocodazole. Thus, the effect of respective lipid structures as a drug delivery system on cells has to be considered in the context of the respective target cell, but in general can be regarded as rather low.